Towards issue centric stakeholder relations and sustainable communication in corporate community engagement and employee volunteering - Johansen, Trine Susanne; Nielsen, Anne Ellerup (Communication & Language at Work, 2024)
Corporate community engagement and employee volunteering are established fields of corporate social responsibility research and practice. Community engagement and employee volunteering aim at enhancing corporation-stakeholder relationships prioritising specific corporate centric, dyadic relations to communities and employees respectively. These dyadic relationships privilege the corporation as the active communicator and decision maker thereby marginalising communities and employees as passive receivers of corporately designed decisions and meaning. In light of existing critiques of corporate centricity, the article’s purpose is to reorient the corporate centric stakeholder approach in community engagement and employee volunteering based on networked, issue centric approaches. The methodology of theory adaptation is applied whereby domain theory (community engagement and employee volunteering literatures) is problematised and reoriented using alternative theoretical conceptualisations referred to as method theory (developments in stakeholder research within corporate social responsibility scholarship). Firstly, it is demonstrated how community engagement and employee volunteering literatures place the corporation at the centre of dyadic relationships to communities and employees respectively. Second, by overlapping community engagement and employee volunteering a corporate community engagement volunteering (CCEV) framework is constructed highlighting corporate centricity and allowing for its problematisation with reference to corporate social responsibility literature. Third, developments in corporate social responsibility stakeholder research are drawn upon in order to reorient the framework placing the issue (and not the corporation) at the centre as the basis for promoting joint decision-making and sustainable communication between stakeholders engaged in corporate community engagement volunteering. The article contributes to community engagement and employee volunteering literatures by reconceptualising community and employee stakeholders and provides researchers and practitioners with a networked approach where the issue, and not the corporation, inspires relationship building. Issue centric stakeholder relations are argued to provide a foundation for sustainable communication practices in which all stakeholders are recognised as active decision and meaning makers.